Modelling foundations and applications : 14th European Conference, ECMFA 2018, held as part of STAF 2018, Toulouse, France, June 26-28, 2018, Proceedings /: 14th European Conference, ECMFA 2018, held as part of STAF 2018, Toulouse, France, June 26-28, 2018, Proceedings. (2018) - Unknown
No abstract available